Investigating Translation Competence: Conceptual and Methodological Issues

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe PACTE group uses empirical-experimental research methods to investigate translation competence and how it is acquired. This article presents the design of our Translation Competence research project and the first results of a pilot test carried out to evaluate our research design and the instruments that will be used in the experiment. The first results of the pilot test are related to decision-taking in the translation process and the interrelation between the use of internal and external support. The results point to differences in the processes followed by professional translators and other language professionals. Furthermore, the pilot test has proved the reliability of our instruments.